THE MOMENT OF TRUTH: END OF THE TRANSITION PERIOD? (On the Democratic Initiative in the Central Asian States) - TOLIPOV, Farkhod (CENTRAL ASIA AND THE CAUCASUS, 2005)
A specter is haunting Central Asia—the specter of democracy. This is how the opening phrase of Marx and Engels’ Communist Manifesto should read in a region soon probably to be engulfed by a wave of “democratic revolutions.” We have already seen the Rose Revolution in Georgia, the Orange Revolution in Ukraine, and the Tulip Revolution in Kyrgyzstan. Journalists and political analysts readily agreed to treat the power changes in post-Soviet states as revolutions inspired by certain foreign funds and organizations or even by Western states.We should bear in mind, however, that the epoch of post-Soviet leaders the newly independent states inherited from Soviet power, who are going on with the old policies, is drawing to an end.